(untitled) (Medical Forum Monthly, 2024)
Objective: To evaluate the common postoperative complications of Lichtenstein mesh repair and laparoscopic TAPP repair in patients with inguinal hernias. Study Design: Randomized controlled trial study Place and Duration of Study: This study at the Department of Surgery, Central Park Teaching Hospital, Lahore from January 2023 to June 2023. Methods: This comparative study was conducted at Central Park Hospital, Lahore. A total of 100 participants were divided into two groups after taking informed consent. Data was entered and analyzed by SPSS 26. Results: The average age of the cases in Group A was 23.70 ± 5.08 and in Group B it was 25.86 ± 4.44. In this study hematoma formation, secrotal edema urinary retention and chronic pain was found significant in both groups with p-value 0.041, 0.022, 0.025 and 0.022 respectively. However, seroma formation, and hernia recurrence was found insignificant with p-values 0.079, and 0.092 respectively. Conclusion: It is concluded that both ways are good for surgery but TAPP is safer, cheaper and time saving with the lesser incidence of post-operative complications and decreased rate of infection.